(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper has critically examined the role of citizens in strengthening the local governance scenario in India with a perspective on rural and urban decentralized institutions under the 73rd and 74th Constitutional Amendments in India. It assesses the citizens’ participation in decision-making processes, participatory budgeting, social auditing, and the use of law and electronic accountability processes like the Right to Information (RTI) Act, 2005. Drawing upon secondary data, government reports, and drawing from case studies in Kerala, Rajasthan, and West Bengal, the study illustrates how the active involvement of citizens improves the transparency, accountability, and responsiveness of local governments. Kerala is one of the best practices in terms of participatory planning and budget allocation, Rajasthan in terms of the impact of social audits on rural development, and West Bengal as an excellent example of urban participatory governance supported by digital tools. The study also highlights socio-economic barriers, a lack of awareness, political interference, and capacity constraints of local bodies as major challenges acting as a hindrance to effective citizen involvement. Based on these insights, the paper is proposing policy recommendations, which include capacity building, inclusive practices, awareness campaigns, and technology-enabled engagement that build citizen roles and strengthen the processes for more accountable, responsible, and equitable local governance in India.